2017
DOI: 10.3390/w9040275
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assessment of Comprehensive Water Quality Considering the Release of Sediment Pollution

Abstract: Abstract:Comprehensive assessment of water quality is an important technological measure for water environmental management and protection. Previous assessment methods tend to ignore the influences of sediment pollutant release and dynamic change of the water boundary. In view of this, this paper explores a new method for comprehensive water quality assessment. Laboratory simulation experiments are conducted to analyze the influences of sediment pollutant release on water quality, and the results are taken as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Despite the increase of the TN concentration in the water, the TN stored in the water decreased during the study period due to the decrease in water volume (from 562 million m 3 in 2009 to 183 million m 3 in 2016), which demonstrated that the TN that accumulated in the sediment contributed to a large proportion of the TN accumulation in the reservoir. Recent research has also shown that TN in the sediment of the Biliuhe reservoir is at a relatively high level, and endogenous nitrogen released from the sediment could contribute to the water nitrogen pollution [54]. Water supply and flood discharge are two major ways to export the TN from the reservoir.…”
Section: Tn Accumulation In the Biliuhe Reservoirmentioning
confidence: 99%
“…Despite the increase of the TN concentration in the water, the TN stored in the water decreased during the study period due to the decrease in water volume (from 562 million m 3 in 2009 to 183 million m 3 in 2016), which demonstrated that the TN that accumulated in the sediment contributed to a large proportion of the TN accumulation in the reservoir. Recent research has also shown that TN in the sediment of the Biliuhe reservoir is at a relatively high level, and endogenous nitrogen released from the sediment could contribute to the water nitrogen pollution [54]. Water supply and flood discharge are two major ways to export the TN from the reservoir.…”
Section: Tn Accumulation In the Biliuhe Reservoirmentioning
confidence: 99%
“…In particular, the ambient water quality can have a significant effect on changes in the microbial food web structure and functions, which involve the biological community composition, hypolimnetic hypoxia/anoxia, and toxic algal blooms in coastal areas [6,7,8,9,10]. On top of the microbial food web changes, sediment contamination is another causal factor affecting the benthic biota, a significant food source for fish [11,12,13,14]. Additionally, resuspension of sediment micro-organisms into the water column can increase the health risk for those who use water [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the release of sediments is gradually considered in water quality assessment [14]. It is proven that pollutants released from sediments can affect the water quality evaluation results and sediments release is a non-negligible factor in water quality simulation and evaluation [15,16].…”
Section: Introductionmentioning
confidence: 99%